E-MODUL INTERACTIVE E-MODUL SUPPORTED BY HEYZINE FLIPBOOK IN MATHEMATICS LEARNING.: INTERACTIVE E-MODUL SUPPORTED BY HEYZINE FLIPBOOK IN MATHEMATICS LEARNING. - della yolanda putri; As Elly S; Yufitri Yanto (Universitas PGRI Silampari, 2025)
This article aims to determine the impact of using interactive e-modules supported by Heyzine Flipbook in mathematics learning on students' learning outcomes and to assess students' mathematical problem-solving abilities. The method used is a Systematic Literature Review (SLR). A total of 12 articles related to the use of interactive e-modules supported by Heyzine Flipbook in mathematics learning from the years 2018 to 2024 were reviewed. These articles were sourced from Google Scholar and the Science and Technology Index (Sinta). The results of this Systematic Literature Review indicate that mathematics learning supported by Heyzine Flipbook can improve students' learning outcomes as well as enhance their mathematical problem-solving abilities.